Leveraging AI for higher education: The role and implications of chatGPT: THE ROLE AND IMPLICATIONS OF CHATGPT - Nguyễn, Ngọc Vũ; Lien (Tạp chí Khoa học HUFLIT, 2023)
As artificial intelligence (AI) spreads across more industries, its potential to revolutionize higher education calls for in-depth investigation. This review paper examines the possible uses, advantages, and difficulties of ChatGPT, an advanced language model created by OpenAI, in the context of higher education. We examine how ChatGPT is used to improve teaching and learning, support professional development, and streamline administrative chores like generating quality assurance reports using a wide range of academic literature. We also take into account any potential negative effects, such as challenges with data privacy, difficulties comprehending complicated ideas, possible false information, and accessibility problems. Finally, we suggest potential uses for ChatGPT in higher education as well as future avenues for research, highlighting its potential as a teaching assistant, a resource for educators' professional growth, and a means of improving administrative effectiveness. Despite several issues that need to be resolved, our analysis indicates that ChatGPT has a great deal of potential to transform the higher education sector.